Studi Literatur: Kesadaran Lingkungan Individu dalam Konteks Penanggulangan Perilaku Membuang Sampah Mikroplastik (Popok Sekali Pakai dan Pembalut Wanita) di Sungai Indonesia - Eko Armada Riyanto; Indah Yasminum Suhanti (Fakultas Psikologi Universitas Negeri Malang, 2021)
Environmental awareness from the individual side was not discussed much in research. Individual environmental awareness is very important to cope the behavior of microplastic waste, in this case it was focused on disposable diapers and sanitary pads. The research method was literature study. The main source was Indonesian research articles on environmental awareness over the past 10 years. Supporting sources were books, handbooks, dictionaries. The analysis method was content analysis. The validity of the data was carried out using theoretical triangulation. The results obtained are environmental awareness discussed with the concept of knowing, understanding, values, then manifested in care and behavior. Environmental awareness was widely discussed in the group area. Individual environmental awareness could be discussed through the philosophy of relationality. For the behavior of taking out trash of disposable diapers and sanitary pads in rivers, the philosophy of relationality provides a view of diminishing knowledge and awareness about the existence of me, and other people as well as the existence of rivers. Suggestions for further research are the expansion of the time span and type of literature. For research related to overcoming environmental pollution behavior in general and specifically in Indonesia, it is necessary to define environmental awareness properly and consider the use of the philosophy of relationality.